Curriculum Development of Madrasah Diniyah - Vania Putri Kusuma Wardany; Istikomah (Adabiyah: Jurnal Pendidikan Islam, 2022)
Madrasah Diniyah is a non-formal educational institution that uses a curriculum that can be developed by the institution itself in accordance with the characteristics of each. The purpose of this studyonly focus on the process, implementation, barriers to curriculum development at Madrasah Diniyah Salafiyah Mamba'us Sa'adah, the type of research using RND (Research and Development), data collection techniques using interview, observation, documentation and library studies. The data analysis technique uses a rocket scale. Based on the results of the study, it can be concluded that Madrasah Diniyah Salafiyah Mamba'us Sa'adah has undergone curriculum development from year to year starting from the objectives, content, methods and learning strategies. Supporting the development of the Madrasah Diniyah Salafiyah Mamba'us Sa'adah curriculum is the existence of Ustad/zah, Santri, complete facilities and support from parents, the community. The obstacles include student discipline, government funds, and inadequate building infrastructure.